PENGARUH LUBANG DAN JUMLAH DISK TERHADAP PERFORMA TURBIN TESLA - Marfizal, Marfizal; Wardianto, Dedi; Sufiyanto, Sufiyanto (ITP Press, 2024)
This research focuses on the effect of holes and the number of disks on the performance of the Tesla turbine, where this experiment uses one Tesla turbine unit with a constant inflow discharge of 0.037 m3/s and a constant load of 50 kg on. Then testing was carried out by varying the number of holes on the disk (4, 6, 8) and varying the number of disks (11,13, 15) with a hole diameter of 10 mm, disk diameter of 160 mm, disk thickness of 0.5 mm. After testing and data analysis, it can be seen that the variations in the number of holes on the disk (4,6,8) and the number of disks factor can be concluded that the maximum power is 310,148 Watts for the number of holes on the disk factor while for the number of disks factor it is 301,154 Watts, where there is a difference of 8,994 Watts. Meanwhile, the maximum efficiency is 73.754 for the number of holes in the disk, while for the number of disks it is 71.652, where there is a difference of 2.102.